220k views
3 votes
Geometry Question attached below

Geometry Question attached below-example-1
User BaronS
by
5.0k points

1 Answer

3 votes

I'm sure there's an easier way to do this, but this method does work:

First, AB = CD = CG + GF + FD, so FG = 2.

By the Pythagorean theorem, in triangle AFD we get


1^2+3^2=A F^2\implies A F=√(10)

and in triangle BCG,


2^2+3^2=BG^2\implies BG=√(13)

Angles AFD and EFG form a vertical pair, so they are congruent and have measure


m\angle EFG=\tan^(-1)3

Similarly, angles BGC and FGE are congruent and have measure


m\angle FGE=\tan^(-1)\frac32

Then the remaining angle in triangle EFG has measure


m\angle FEG=\pi-\tan^(-1)3-\tan^(-1)\frac32

We can solve for the lengths of FE and GE exactly by applying the law of sines:


\frac{\sin\left(\pi-\tan^(-1)3-\tan^(-1)\frac 32\right)}2=(\sin\left(\tan^(-1)3\right))/(GE)=(\sin\left(\tan^(-1)\frac32\right))/(FE)


\implies GE=\frac{2√(13)}3,FE=\frac{2√(10)}3

Let
s be the semiperimeter of triangle ABE, so that


s=\frac{AB+BE+EA}2

Then according to Heron's formula, the area of triangle ABE is


√(s(s-AB)(s-BE)(s-EA))=\frac{25}2

Geometry Question attached below-example-1
User Mayjak
by
5.8k points